Fast deterministic consensus in a noisy environment. - Aspnes, James
It is well known that the consensus problem cannot be solved deterministically in an asynchronous environment, but that randomized solutions are possible. We propose a new model, called noisy scheduling, in which an adversarial schedule is perturbed randomly, and show that in this model randomness in the environment can substitute for randomness in the algorithm. In particular, we show that a simplified, deterministic version of Chandra's wait-free shared-memory consensus algorithm [Chandra, in: Proceedings of the Fifteenth Annual ACM Symposium on Principles of Distributed Computing, Philadelphia, PA, USA, 23?26 May, 1996, pp. 166?175] solves consensus in time at most logarithmic in the number of active processes. The proof of termination is based on showing that a race between independent delayed renewal processes produces a winner quickly. In addition, we show that the protocol finishes in constant time using quantum and priority-based scheduling on a uniprocessor, suggesting that it is robust against the choice of model over a wide range.
Keywords: Consensus; Agreement protocols; Randomized algorithms; Distributed computing; Wait-free.; Shared memory; Perturbation analysis; Noisy scheduling